2016
DOI: 10.1039/c6ra05090e
|View full text |Cite
|
Sign up to set email alerts
|

TiO2sol-embedded in electroless Ni–P coating: a novel approach for an ultra-sensitive sorbitol sensor

Abstract: A Ni–P/Ni–P–TiO2 coating was readily prepared by direct incorporation of nano-TiO2 sol into a Ni–P solution for electroless deposition and applied as a novel electrode for sensitive sorbitol sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Owing to its abundance, low toxicity, chemical and thermal stability, and resistance to photocorrosion, TiO 2 has been extensively studied as a catalyst for different photocatalytic reactions, [1][2][3][4] and used for paints, 5 coatings, 6 supports for drug delivery, 7 angiogenic agents 8 and so on. Crystalline TiO 2 itself has limited practical applications as a photocatalytic material because its activity is driven by ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its abundance, low toxicity, chemical and thermal stability, and resistance to photocorrosion, TiO 2 has been extensively studied as a catalyst for different photocatalytic reactions, [1][2][3][4] and used for paints, 5 coatings, 6 supports for drug delivery, 7 angiogenic agents 8 and so on. Crystalline TiO 2 itself has limited practical applications as a photocatalytic material because its activity is driven by ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The utilization of silver nanoparticles (AgNPs) that are prepared using environmental biodegradable polymers as both reductant and stabilizer [11][12][13][14] contributes to an improvement in the number of particles per unit region and thus, improve the antibacterial activity. [15][16][17][18][19][20] Because of the abundance of proteins containing sulfur on the bacterial cell membrane, AgNPs can react with proteins containing sulfur inside or outside the cell membrane, which in turn affects the viability of bacterial cells. It has been also suggested that silver ions (Ag + ) generated from AgNPs may interfere with phosphorus moieties in DNA, resulting in inactivation of DNA replication, or may respond with proteins containing sulfur, contributing to enzyme function inhibition.…”
mentioning
confidence: 99%
“…The method used for preparation of TiO 2 sol was previously described [86,87]. Initially, 0.025 mol of TIAA and 0.025 mol of 1,3 propanediol were mixed together and refluxed at 85 C for 60 min with continuous magnetic stirring.…”
Section: Synthesis Of Tio 2 Solmentioning
confidence: 99%
“…The TiO 2 sol-GO solution was used to prepare an electroless NiP solution. The preparation details of electroless Ni-P solution has been described in the previous report [87]. The electroless bath composition is shown in Table 3.1.…”
Section: Preparation Of Electroless Nip-tio 2 Sol-rgo Plating Bathmentioning
confidence: 99%